URGENSI PEMAHAMAN STATISTIK DAN STATISTIKA DALAM PENDIDIKAN DASAR - Nurhaswinda, Nurhaswinda; Cahyani, Meilana; Herly, Adinda Dwiyana; Meiwati, Lutfia; Lestari, Yessi; Anum, Fatma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Statistical literacy is an important competency in elementary mathematics education, yet students’ understanding remains limited. Statistics learning is often procedural and lacks contextual data interpretation. This study aims to examine the urgency of understanding statistics and statistics education in elementary schools based on previous research findings. A qualitative approach using a literature review method was employed. Data were collected from national and international journal articles, reference books, and relevant educational policy documents. The results indicate that although statistical literacy has been integrated into the elementary school curriculum, students’ abilities in interpreting, presenting, and drawing conclusions from data are still low. However, innovative, contextual, and participatory statistical learning approaches have proven effective in improving students’ statistical literacy. Therefore, strengthening statistics education from the elementary level is essential to support numeracy skills and data-based reasoning.